1991
DOI: 10.1128/jcm.29.12.2887-2889.1991
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of virulent Rhodococcus equi in isolates from soil and feces of horses from horse-breeding farms with and without endemic infections

Abstract: The prevalence of virulent Rhodococcus equi in isolates from soil and feces of foals on a farm with endemic R. equi infections was significantly higher than that of a farm with no history of the disease. Foals bred on a farm with the endemic disease might be constantly exposed to virulent R. equi in their environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 7 publications
2
51
0
2
Order By: Relevance
“…Although all horse farms are likely to be infected with R. equi, clinical disease ranges from enzootic and devastating on some farms, to sporadic or undiagnosed on others. This may reflect differences in environment (temperature, irritant dust, soil pH) and management conditions, as well as differences in the virulence of isolates (Takai et al 1991). Rhodococcus equi may be found in areas never inhabited by horses, although greater concentrations occur where horses are present.…”
Section: Discussionmentioning
confidence: 99%
“…Although all horse farms are likely to be infected with R. equi, clinical disease ranges from enzootic and devastating on some farms, to sporadic or undiagnosed on others. This may reflect differences in environment (temperature, irritant dust, soil pH) and management conditions, as well as differences in the virulence of isolates (Takai et al 1991). Rhodococcus equi may be found in areas never inhabited by horses, although greater concentrations occur where horses are present.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PCR rapidly and accurately identifies and distinguishes between virulent and avirulent strains of R. equi by detection of the VapA gene (Anzai et al, 1997;Sellon et al, 2001). However, PCR may result in false-positives due to detection of very small numbers of R. equi that are present as environmental contaminants because the organism is ubiquitous and present in the soil and horse dung of most horse farms (Takai et al, 1991b). Moreover, decrease in sensitivity of PCR amplification has been experienced due to the presence in clinical samples of substances (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Farms with endemic R. equi pneumonia are heavily contaminated with virulent R. equi, while the others are not, although avirulent R. equi are frequently found in environment and feces on every farm (Takai, 1997). This implies that foals on farms with endemic R. equi pneumonia are frequently exposed to high numbers of virulent bacteria (Takai et al, 1991b;Takai, 1997). Yet, the actual proportion of virulent strains in the environment is no indication for the prevalence of R. equi pneumonia (Martens et al, 2000;Takai et al, 2001a;Muscatello et al, 2006a;Cohen et al, 2008).…”
Section: Epidemology Of R Equi In Horse Infectionsmentioning
confidence: 99%